Does antiretroviral therapy initiation increase sexual risk taking in Kenyan female sex workers? A retrospective case–control study. Issue 2 (1st April 2012) - Mawji, Elysha; McKinnon, Lyle; Wachihi, Charles; Chege, Duncan; Thottingal, Paul; Kariri, Anthony; Plummer, Francis; Ball, T Blake; Jaoko, Walter; Ngugi, Elizabeth; Kimani, Joshua; Gelmon, Lawrence; et al.
Abstract : Objectives: Although antiretroviral therapy (ART) prolongs life and reduces infectiousness, in some contexts, it has been associated with increased sexual risk taking. Design: Retrospective case–control study. Setting: Nairobi-based dedicated female sex worker (FSW) clinic. Participants: HIV-infected FSWs before and after ART initiation (n=62); HIV-infected and -uninfected control FSWs not starting ART during the same follow-up period (n=40). Intervention: Initiation of ART. Primary outcome measures: Self-reported condom use, client numbers and sexually transmitted infection incidence over the study period (before and after ART initiation in cases). Results: Sexual risk-taking behaviour with casual clients did not increase after ART initiation; condom use increased and sexually transmitted infection incidence decreased in both cases and controls, likely due to successful cohort-wide HIV prevention efforts. Conclusions: ART provision was not associated with increases in unsafe sex in this FSW population.